(untitled) (Global Journal of Management and Business Research, 2018)
This paper evaluates the advisability of a monetary union in Latin America applying the theory of optimum currency areas (OCA). The analysis, based on the traditional OCA criteria, suggests that there is no evidence for any monetary integration in Latin America, even at a subregional level. Latin American countries have evidenced a low degree of trade integration and asymmetric co-movements among their shocks. Moreover, important differences in the speed of adjustment and size of shocks are found. Higher policy coordination seems to be necessary before starting any economic integration process in Latin America.